Innovative husk-crete building materials from rice chaff and modified cement mortars (2020)
The study considers the use of rice chaff s (husks) as an aggregate in a composite cement matrix system. Cement mortars were modifi ed using styrene butadiene rubber polymer for strengthening. The goal is to develop a lightweight building material with good thermal insulation properties out of agricultural waste. The compressive strength, split tensile strength and fl exural strength were experimentally evaluated. Further analyses of the samples were carried out by means of scanning electron microscope and energy dispersive spectroscopy. The key results obtained were presented and analysed with the performance of the proposed husk-crete building material showing adequate properties essential for a lightweight structural material with possible applications for non-structural purposes.